SEGI-SEGI POKOK HAM DALAM KUHAP - Said Abdullah (Jurnal LEX SPECIALIS, 2010)
AbstractWhereas in the Criminal Procedure Code has contained the principle of protecting human rights. The existence of the core principles of human rights in the legislation does not make much sense if not protected and enforced by the courtse